2020
DOI: 10.26832/24566632.2020.050405
|View full text |Cite
|
Sign up to set email alerts
|

Agro-morphological characterization of flax (Linum usitatissimum L.) accessions at north-western part of Bangladesh

Abstract: Flax (Linum usitatissimum L.), grown throughout the world for millennia. It is a multipurpose agricultural crop that can provide food, fuel and fibre. An agro-morphological characterization based on 13 traits of 26 flax accessions was carried out during the Rabi season 2017-2018 at the Agricultural Research Station, Bangladesh Agricultural Research Institute, Rangpur. The field experiment was laid out in a randomized completed block design having four replications. Flax seeds were sown in 3.0 m × 0.6 m plot wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…1), implying that future breeding programs will have a larger opportunity to utilize these characteristics [41]. In agreement with the present study results, significant variability in yield and its related attributes of linseed were also reported by other researchers including our previous study with 26 linseed accessions [35,36,42]. We obtained that the phenotypic variance (σ 2 p) had been always higher than the genotypic variance (σ 2 g) for all of the studied traits (Table 3), indicated that the environmental factors regulated the expression of traits in linseed.…”
Section: Discussionsupporting
confidence: 92%
“…1), implying that future breeding programs will have a larger opportunity to utilize these characteristics [41]. In agreement with the present study results, significant variability in yield and its related attributes of linseed were also reported by other researchers including our previous study with 26 linseed accessions [35,36,42]. We obtained that the phenotypic variance (σ 2 p) had been always higher than the genotypic variance (σ 2 g) for all of the studied traits (Table 3), indicated that the environmental factors regulated the expression of traits in linseed.…”
Section: Discussionsupporting
confidence: 92%